ANTIOXIDANT AND CYTOTOXIC EFFECTS OF ESSENTIAL OILS EXTRACTED FROM Viola odorata L. CULTIVATED IN IRAQ - Zainab O. Salman,; Shaymaa I. K. Al-juboori,; Bushra M.J. Alwash, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to determine the composition of essential oil contained in Viola odorata flowers and leaves. As well as assessing the cytotoxic effects of this oil on cancer cells and its antioxidant properties. A GC-Mass analysis was conducted to reveal essential oil components in flowers and leaves. For testing the antioxidant capacity of flowers and leaves oil, DPPH (1,1 Dyphenyl-2-picrylhydrazyl), resazurin dye, and hydroxyl were used. An in vitro study was conducted using lung cancer (A549) and breast normal (MCF-10) cell lines with concentrations of 25, 50, 100, 200, and 300 µl/ml of V. odorata L. essential oil.   According to the results, essential oils derived from flowers and leaves contain different components in terms of quality and quantity. At a concentration of 300 µl/ml, the results showed that flowers' essential oil was highly antioxidant (98.16 %, 92.47%, 94.00 %) when combined with DPPH, resazurin dye, and hydroxyl, respectively. There was variation in cytotoxic effects on cancer cells based on oil concentrations and sources (flowers and leaves). In conclusion, the A549 cell line was significantly affected by flower oil than by leaves oil. The highest effect of flower oil was observed at a concentration of 300 µl/ml.